Simultaneous Determination of Phenolic Acids, Anthraquinones, Flavonoids, and Triterpenes of Cynomorii Herba in Different Harvest Times by LC-MS/MS - Hua Jin; Ge Tang; Jin Li; Lin Ma; Yuhong Li; Yan-xu Chang (Journal of Analytical Methods in Chemistry)
A sensitive and accurate method was developed for the simultaneous determination of twelve components including phenolic acids (gallic acid, protocatechuic aldehyde, protocatechuic acid, and ferulic acid), flavonoids (catechin, epicatechin, rutin, luteolin, luteolin-7-glucoside, and epicatechin gallate), anthraquinones (emodin), and triterpenes (ursolic acid) in Cynomorii herba in different harvest times by liquid chromatography tandem mass spectrometry (LC-MS/MS). The chromatographic separation was achieved on an Eclipse plus C18 (3.0 mm × 50 mm, 1.8 μm) column at 40°C. The mobile phase consisted of acetonitrile and 0.05% formic acid with a gradient elution at a flow rate of 0.4 mL·min −1. Under the optimized conditions, there was good linear relation (r ≥ 0.9944) and satisfactory precision (RSD values less than 5.65%). The recoveries of the twelve components were in the range of 93.5–105%. Moreover, the limits of detection (LOD) ranged from 0.003 to 21 ng mL−1 for the twelve analytes. In conclusion, the validated method was successfully applied to analyze the change regularity of the twelve components of Cynomorii herba in different harvest times. It provides a theoretical basis for choosing the suitable harvesting time of Cynomorii herba.